Ni(II), Pd(II) and Cu(II) Complexes with N-(dialkylthiocarbamoyl)-N’-picolylbenzamidines: Structure and Activity against Human MCF-7 Breast Cancer Cells - Nguyen, H. H.; Le, C. D.; Pham, C. T.; Trieu, T. N.; Hagenbach, A.; Abram, U. (My University, 2012)
Ni(II), Pd(II) and Cu(II) Complexes with N-(dialkylthiocarbamoyl)-N’-picolylbenzamidines: Structure and Activity against Human MCF-7 Breast Cancer Cells
Keywords: Ni/Pd/Cu Complexes